LEVELS OF AGRICULTURAL RESOURCE DEVELOPMENT IN SATARA DISTRICT: A REGIONAL DISPARITY (International Journal of Food and Nutritional Sciences, 2022)
Agricultural resources play a significant role in the exploitation of basics resources and conservation at any stage. Agricultural resource development is considered as a basics factor in the processes of national development. Satara district is well known district in western Maharashtra, but the levels of Agricultural Resource development is medium class in satara district KaradTahsil has first rank in Agricultural resource development, because development of Irrigation, Agro based industries, infrastructural facilities, Fertilizers, are largest proportion as compared to other tahsils. Lowest Agriculture resource development is found in Mahableshwar, Khandala and Javali tahsils, because these are high rain fall, and other physiographic conditions